La vulneración de derechos constitucionales del alimentante en el juicio de alimentos” - Erazo Celi, Gonzalo Fernando (2016)
This research is based primarily on the conflict generated by the law when, in an effort to protect the integrity of the child, violates the rights of those who are obliged to provide food, regardless of the economic capacity of the obligor. The National Council for Childhood and Adolescence, sets the values to pay, if food trial, by the applicant. These rates vary depending on the age and number of food; and income of the respondent. Now, if indeed you can not forsake the child under any circumstances, it is also true that many times the defendant is not in economic capacity to respond or comply with its obligation in the manner established by the Pension Table Low Food, approved by the National Council for Childhood and Adolescence and now by the Ministry of Economic and Social Inclusion, so much so, that a high percentage of defendants are deprived of freedom for failing to fulfill their obligations and others are left without resources to meet their basic as needs are food, housing, health, clothing. For this, a study of judgments of food presented in the city of Zamora in 2013, with the assumptions that were made in this investigation it was concluded so unequal treatment of rights was made it was found obligor must also be covered by the Act for in the relationship created to ensure the right to food, there are two subjects that are the obligor and the food must be deemed to equal opportunities both in the practice of law and in the exercise of defense principles that should not be absent in the development of a conflict that is generated in law and obligations that must be perfectly under certain concepts of equity and fairness to both parties. So we made a proposal to amend Article 15 of the Act of the Code of Childhood and adolescence in which a new clause be included to protect the obligor, you may have a decent life and do not order the begging